Aspectos inorgânicos e físico-químicos na determinação espectrofotométrica do radical 1,1-difenil-2-picrilhidrazil. - Menezes, Bryan Brummelhaus de (2020)
The DPPH method has been reported with misconceptions in a large number of studies, precluding the direct comparison of results. Attention is drawn to a common mistake in the unit used to express the IC50 value of ascorbic acid and other antioxidant substances. Concentration of the antioxidant is widely misused disregarding the DPPH• concentration, while the molar ratio of antioxidant/DPPH• is de correct choice. Data from 25 studies with widely varying IC50 values were renormalized according to reaction stoichiometry, resulting in values more coherent and closer to the ideal one of 0.25 for at least 15 of them. In addition, the model currently used to calculate the DPPH• concentration can lead to an overestimation of around 7%, as it does not take into account the small contribution of the reaction product. In view of that, we present a mathematical model to correct the overestimation of the DPPH• concentration.